Analysis of Behavioral Factors Influence The Audit Judgment - Sukiswo, Helmy Wahyu; Rachman, Helmy Aulia (Journal of Economics, Business, and Government Challenges, 2023)
Personal characteristics of audit judgment refer to individual traits that can influence the auditor's decision in making audit decisions. Some of the personal characteristics that are relevant in this context include personal risk assessment, level of confidence, technical knowledge, professional ethics, and communication and social interaction skills. The level of confidence plays an important role in making audit decisions, with auditors who are more confident tend to be more likely to take risks in issuing audit opinions. Strong technical knowledge is a prerequisite for producing accurate and up-to-date audit assessments. Professional ethics are the foundation for maintaining the independence and integrity of the auditor, while communication and social interaction skills are necessary to collaborate effectively with the audit team and clients. Overall, the auditor's personal characteristics have a significant impact on the quality and integrity of the audit results produced.